Religious Activity and Mechanisms of Personality’s Psychological Defense - Savelyuk, Natalia (Psychological Prospects Journal, 2017)
The article reveals theoretic analysis of the mechanisms of personality’s psychological defense in the context of their connection with the levels of religious activity. Contradictory empirical data of the researchers from several different countries have been taken into consideration. Results of author’s empirical research conducted on a representative sample of Ukrainians have been described and analyzed. The fundamental methods and techniques are «The measuring technique of religious activity» by D. O. Smirnov and the «Life Style Index» (R. Plutchik, H. Kellerman, J. Conte). Four subgroups of examinees have been singled out on the first stage: with the lowest level of religious activity (138), with a lower than average (141), with a higher than average level (139) and with the highest level of religious activity (125). Tension indicators of each mechanism of psychological defense in particular and the very tension of representatives of all four subgroups in general have been stated on the second stage. First of all, it has been established that Ukrainians are characterized by a rather high total indicator of the intensity of defense psychological mechanisms – an average of about 60 %. At the same time, regardless of the level of RA, the most influential are projection, the least influential are regression and substitution. Due to the results of the application of methods of mathematical and statistical processing of data (Kruskal–Wallis one-way analysis of variance) the following conclusions have been made: along with the growth of religious activity, the psychological mechanism of hypercompensation increases most substantially, then – the mechanisms of denial and rationalization. However, weakening of the action of compensation have also been observed. It is generally stated that at the higher levels of religious activity of the investigated Ukrainians the most influential are mainly constructive psychological mechanisms, and this completely resonates with the humanistic axiological potential of the Christian religion.